2014
DOI: 10.1007/s11357-014-9720-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single vs. multiple-set short-term strength training in elderly women

Abstract: The strength training has been shown to be effective for attenuating the age-related physiological decline. However, the adequate volume of strength training volume adequate to promote improvements, mainly during the initial period of training, still remains controversial. Thus, the purpose of this study was to compare the effects of a short-term strength training program with single or multiple sets in elderly women. Maximal dynamic (1-RM) and isometric strength, muscle activation, muscle thickness (MT), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 53 publications
11
40
0
Order By: Relevance
“…Our data suggest the intra-rater reliability of these US parameters is good, especially for MT. The high ICCs (0.88) and low CV and SEM values (<10%) were comparable to the reliability of previous US studies examining MT of quadriceps muscles in young men and elderly women 3 - 5 . This study was designed to assess reliability in young women, including a high number of subjects and using a more robust statistical approach.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Our data suggest the intra-rater reliability of these US parameters is good, especially for MT. The high ICCs (0.88) and low CV and SEM values (<10%) were comparable to the reliability of previous US studies examining MT of quadriceps muscles in young men and elderly women 3 - 5 . This study was designed to assess reliability in young women, including a high number of subjects and using a more robust statistical approach.…”
Section: Discussionsupporting
confidence: 74%
“…Although this study had shown good reliability for EI in a large range of regions of interest, they only carried out ICC and CV analysis in 10 women. Other studies 3 - 5 have demonstrated high ICC (>0.90) and low CV (<5%), but they were conducted as part of a larger study in which reliability was not the primary aim and potential sources of bias might not have been adequately controlled (i.e., measures by blind rater).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar increase in 1RM strength between 1 and 3 set observed in our study is consistent with previous studies that investigate the effect of training volume in trained and Effects of training volume: a contralateral control study untrained subjects 6,9,[12][13][14] . For example, Hass, Garzarella, de Hoyos, Pollock6 showed a similar increase in leg extension 1RM for 1 (+13.6%) and 3 sets (+12.8%) after a 13-wk RT program (8-12 repetitions to volitional fatigue at 75% of 1RM) in previously trained subjects.…”
Section: Discussionsupporting
confidence: 93%
“…These inconsistencies may be associated with the studied muscle groups because different strength gains have been observed in lower-and upper-body muscles in response to training volume 3,5,9,10 . In a specific analysis for lower-body muscles (e.g., knee extensor muscles), some studies have reported greater strength gains with high-volume training than low-volume (3 sets vs.1 set) 3,5,11 , whereas others reported similar results 6,9,[12][13][14] . Therefore, there is a still controversy as to whether multiple sets protocols are more effective than single set protocols for increasing lower-body muscle strength.…”
Section: Introductionmentioning
confidence: 99%